Neurotoxicity of Aluminum - Niu, Qiao. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book reviews the scientific literature and the authors' own research linking aluminum neurotoxicity with cognitive impairment and Alzheimer's disease (AD). It focuses on aluminum levels in the brain, region-specific and subcellular distribution, its relation to neurofibrillary tangles and amyloid beta-the pathological features of AD, and the possible mechanism of aluminum inducing these pathological features. Further, the book stresses the importance of aluminum's complex speciation chemistry in relation to biology, and details aluminum's mechanism in oxidative stress and cell death, especially in connection with apoptosis and necroptosis. The electrophysiological variation and synaptic plasticity induced by aluminum are covered, while the metal's debatable role in AD and the cross-talk between aluminum and genetic susceptibility are also discussed, and more recently the relationship between aluminum-induced epigenetic modification on DNA and non-coding RNAs and neuron death and synaptic impairment. The second edition updates eight chapters according to the most recent researches. Content about aluminum-induced AD-like pathological features, neurotoxic effects of aluminum and aluminum alloy nanoparticles(TBD) and alumina nanoparticles induced neurotoxic and neurodevelopmental toxic effects is also added. In closing, this book provides readers with a systematic summary of aluminum neurotoxicity.
Chapter 1 Overview of the relationship between aluminum exposure and health of human being.-Chapter 2 The Chemistry of Human Exposure to Aluminum -- Chapter 3 Entry and Deposit of Aluminum in Brain -- Chapter 4 Aluminum as a CNS and immune system toxin across the life span.-Chapter 5 Occupational exposure to aluminum and cognitive impairment -- Chapter 6 Debated relationship between Exposure to Aluminum in Daily Life and Alzheimer's Disease -- Chapter 7 Animal Model of Aluminum-Induced Alzheimer's like Disease -- Chapter 8 Aluminum-induced AD-like Pathological Features.-Chapter 9 Aluminum induced neural cells death -- Chapter 10 Aluminum-Induced Electrophysiological Variation, Synaptic Plasticity Impairment, and Related Mechanism.-Chapter 11 Cross Talk Between Aluminum and Genetic Susceptibility -- Chapter 12 Epigenetic modification in aluminum-induced neuron death and synaptic impairment -- Chapter 13 Neurotoxic effects of aluminum and aluminum alloy nanoparticles(TBD) -- Chapter 14 Alumina nanoparticles induced neurotoxic and neurodevelopmental toxic effects.
Keywords: Neurosciences; Pharmacology; Neuroscience; Pharmacology